Influência do nitrogênio adicionado por SHTPN na resistência à erosão por cavitação do aço inoxidável martensítico - Maftoum, Ricardo de Almeida (2012)
Several studies are being done to improve the cavitation erosion resistance of steel. Among those studies, is the use of steels with nitrogen enriched surfaces. In this study the use of SHTPN (Solution Heat Treatment after Plasma Nitriding) technique was studied, which consists in performing plasma nitriding, used to add nitrogen to the material, followed by a solubilization treatment so that the nitrogen is in solid solution. On this experiment two martensitic stainless steel were used (ASTM CA-6NM and ASM 15-5PH). Nitriding was performed at 630°C for 3 hours. Three different solubilization conditions were used for CA6NM steel (1100°C for 1 hour, NS1, 1200°C for 30 minutes, NS2 and 1200° for 1 hour, NS3). Only one condition was used for 15-5PH steel (1200°C por 30 minutos, NS), and later used an aging treatment (390°C for 8 hours, NSE). The samples were analyzed through x-ray diffraction, optical microscopy and microhardness profiles. All CA6NM samples had an increase in surface hardness, and no big austenite presence was observed. On 15-5PH steel, an austenictic phase was observed. The cavitation test was conducted according to ASTM G32/09 standard, but using the indirect method. The damaged area of the samples was analyzed by scanning electron microscopy. The treatment increased cavitation erosion resistance of all samples, having increased over 5 times for the NS1 sample and 3 times for NSE sample.